The Impact of Social Media Marketing on Purchase Intention at PT. Nomaden Cipta Mahardika - Faronsyah, Airul Septian; Taufik Hidayah, Riski (International Journal of Science, Technology & Management, 2025)
Along with the development of information technology, consumers' need to seek information is increasingly greater. Consumers in the architectural services sector also look for information about aesthetic and functional housing via social media. Using Instagram, companies like Nomaden leverage social media marketing to drive consumer purchase intent. This research analyzes how social media marketing influences the architectural services sector to increase purchasing intentions.This research also uses independent variables, namely social media marketing and distribution intensity, which are mediated by the variables brand awareness, quality perception, brand association, brand trust, consumer brand involvement (CBE), and the dependent variable, namely purchase intention. This variable refers to a research titled The Impact of Social Media Marketing on Brand Awareness, Brand Involvement and Purchase Intention in Developing Countries and The Impact of Social Media Communication on Consumer-based Brand Equity and Purchase Intention during the Pandemic. The population in this research is followers of the Nomaden Architect's Instagram account (@nomaden.designstudio). The sample that will be studied is a minimum of 385 respondents using non-probability sampling. This research instrument uses a validity test based on the Product Moment Correlation or Pearson Correlation formula, reliability using the Cronbach alpha technique, descriptive analysis using a continuum line, and verification analysis using a structural equation model with the help of SMART-PLS 4.0.